APPLICATION OF ACTION RESEARCH IN THE TEACHING/LEARNING PROCESS FOR THE ACQUISITION AND DEVELOPMENT OF COMPETENCES: ATTITUDES OF STUDENTS - PROSPECTIVE TEACHERS - Bankauskiene, Nijole; Masaitytė, Ramunė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The profession of teacher requires a qualitative and special preparation for a specific activity. Therefore, the importance of professional and general competencies of relevant specialists working and intending to work in educational institutions is emerging.The document “Common European Principles for Teacher Competencies and Qualifications” (2005) emphasizes the provision that all educators must be able to work effectively in three overlapping areas of activities: working with information, technology and knowledge, working with people (students, colleagues and other partners), working with society and in society at local, regional, national, European and global levels (Saulėnienė, Žydžiūnaitė, & Katiliūtė, 2006). In order to work successfully, the educator must have cognitive, functional, personal and ethical competencies.In Lithuania, changes and updates of regulations, models and conception of the training and activity of teachers are regularly updated (2004; 2010; 2012; 2015; 2016; 2017; 2018). Teachers’ competencies are summarized in the “Description of Professional Competencies of Teachers” (January 15, 2007); the description highlights common cultural, vocational pedagogical and general competences. In many Lithuanian higher education institutions that train qualified educators, since 2000 the method of improving the action research is used in the study process. This method of qualitative research is also highly appreciated and successfully used by different types of schools in the process of specialist education in many foreign countries. This method is also applicable to general education institutions. This method is described and analysed by Lewin (1948), Corey (1953), Grundy (1988), Callhoun (1994), McLaughlin (1997), Lanshear and Knobel (2004), Kemmis and McTaggart (2005), Creswell (2008), Mills and Ainassian (2009) and others.The aim of this article is to analyse the teachers’ opinion on the application of action research in the study process.To achieve the goal, three objectives have been set:1. to discuss the coherence between the European Qualifications Framework (2005) and the Competences of the Lithuanian teachers (2007);2. to highlight the essence of the method of action research;3. to examine how the students themselves – present and future educators – evaluate the method of action research that proves advantageous to acquire and develop competences.The research analysed 102 reports – final study projects on the improvement of the activity of educators prepared by the students – future educators – of one of Lithuanian higher education institutions from 2007 to 2017. The research was carried out in May 2018.It has been established that in the process of the action research, the educators mostly improved these general competencies of – research activities, reflecting and learning to learn, communication and cooperation; these professional pedagogical competencies as the development of professional development, the use of information technology, recognition of understanding the pupil and his/her progress, motivating and supporting students, planning and improving the content of the subject, teaching/learning process management, assessment of student achievements and progress.In all of the 102 projects submitted by the students, the application of this method in the study process at the higher education institution was positively evaluated.It was emphasized that during this research not only the new knowledge was gained, but also the participants of the research, the learners, have themselves developed and improved, as well the researchers – students – future educators have improved.